The role of Creativity and Talent in art education of School Students (Journal of the College of Basic Education, 2022)
Previous studies have shown that learning arts have a significant positive effect on student creativity through using a suitable curriculum. It has been found that arts have become an important and essential part of developing the creativity of students, as it helps the the students to build their confidence and knowledge and to engage with other children. Moreover, it provides them with the necessary skills to develop their creativity through using curricula that were made specifically for teaching arts. This paper reviews the role of creativity in art education, and the role of art on the development of students’ talents. Also, this paper reviews the role of teaching techniques in enhancing and developing the art creativity of students. In addition, the students’ experiences and their exposer to different teaching concepts is how they can achieve full potential creativity and talent.